ChemInform Abstract: Synthesis of Triborylalkenes from Terminal Alkynes by Iridium‐Catalyzed Tandem C—H Borylation and Diboration. Issue 12 (March 2016) - Lee, Chun‐I; Shih, Wei‐Chun; Zhou, Jia; Reibenspies, Joseph H.; Ozerov, Oleg V.
Abstract: The two‐step approach for the synthesis of triborylalkenes starts with the conversion of terminal alkynes and pinacolborane (HBpin) into alkynylboronate catalyzed by a SiNN pincer ligand supported iridium complex, followed by treatment of the reaction mixture with CO for the generation of a new catalyst.